Moth flies (Diptera, Psychodidae) of Estonia - Jozef Oboňa; Olavi Kurina; Ilmar Süda; Jan Ježek (ZooKeys)
A fundamental prerequisite for understanding and protecting biodiversity is the construction of a high-quality faunal database. The primary objective of this study was to address knowledge gaps in the biodiversity of the family Psychodidae in Estonia. Faunistic data on 45 species of moth flies (Diptera: Psychodidae) from Estonia are presented, including 30 new country-records. Sixteen species are considered important for nature conservation. An updated checklist of the family, comprising 71 species, is provided for the Baltic countries. Habitus photographs of selected Estonian species are also included.